2011
DOI: 10.1167/iovs.10-5600
|View full text |Cite
|
Sign up to set email alerts
|

Functional Neuroimaging to Characterize Visual System Development in Children with Retinoblastoma

Abstract: Longitudinal functional neuroimaging demonstrated important effects of disease and treatment. Therefore, fMRI and DTI may be useful for characterizing the impact of retinoblastoma on the developing visual system and improving the prediction of visual outcome in survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 73 publications
5
20
0
Order By: Relevance
“…36 Finally, cortical dominance corresponding to the projection from the nasal hemiretina in the remaining eye has been found in enucleated children. 37 These findings are consistent with the hypothesis that a lack of binocular competitive and inhibitory interactions allows the remaining eye to recruit visual neurons associated with the enucleated eye, resulting in cortical reorganization of the visual system after early ME.…”
supporting
confidence: 89%
“…36 Finally, cortical dominance corresponding to the projection from the nasal hemiretina in the remaining eye has been found in enucleated children. 37 These findings are consistent with the hypothesis that a lack of binocular competitive and inhibitory interactions allows the remaining eye to recruit visual neurons associated with the enucleated eye, resulting in cortical reorganization of the visual system after early ME.…”
supporting
confidence: 89%
“…Very few studies analyzed functional consequences of enucleation (Toldi et al, 1989; Olavarria et al, 2007; Barb et al, 2011; Kozanian et al, 2015). One of these is from Toldi et al (1989) in which they recorded rats into the lateral portion of the V1, in the cortex contralateral to the removed eye.…”
Section: Callosal Plasticity: How Visual Input Impacts On Interhemispmentioning
confidence: 99%
“…Another study by Barb et al (2011) has used DTI to investigate structural features of the CC in subjects with retinoblastoma, a childhood cancer of the eye. The authors found evidence for disruption of white matter maturation, in particular patients with bilateral retinoblastoma had greater deficits compared to those with unilateral disease.…”
Section: Callosal Plasticity: How Visual Input Impacts On Interhemispmentioning
confidence: 99%
See 1 more Smart Citation
“…Current high‐field MRI scanners (3 T or higher) and parallel imaging technique offer improved sensitivity on DTI measurement and become increasingly popular in clinic, greatly facilitating the examination of optic nerve in child patients. In addition, the monkey DTI measurement and analysis are translational and the data might be used as a reference in clinical study, as DTI investigation of optic nerve in children at very early age could be invasive because an invasive procedure, sedation, is required for children under 4 years old to reduce motion artifacts during scanning (Barb et al, 2011).…”
Section: Discussionmentioning
confidence: 99%